Enhancing soil fertility in urban green spaces via cellulolytic microbial-organic synergies - Xu, Zhaofeng; Dai, Jiawei; Yang, Ning; Fan, Yongjie; Shan, Xin; Diao, Yuting; Pan, Xiaocui; Zhao, Lei; Zhao, Jiahui; Ma, Meiqi; Li, Xiang; Xiao, Ming; et al. (Frontiers in Microbiology, 2026)
Urban green spaces (UGSs) are essential for ecological functioning, yet their soils often suffer from limited nutrient cycling due to the slow decomposition of plant litter. While cellulolytic bacteria can promote litter breakdown by enhancing cellulose degradation, their effectiveness in urban soils remains limited. In this study, we examined whether combining Bacillus cereus B9, a cellulolytic strain, with vermicompost could improve litter decomposition and soil quality in UGS soils. A pot experiment was conducted with four treatments: control (CK), B9 alone (B9), vermicompost alone (V), and their combination (VB9). Results showed that the VB9 treatment significantly enhanced litter decomposition, cellulase activity, and nutrient availability compared to either treatment alone. Genome sequencing revealed that B9 carries key cellulase genes, including those encoding endoglucanase and β-glucosidase. Enzyme assays confirmed its cellulolytic activity. Co-application also enriched bacterial taxa associated with cellulose degradation, whose abundance was positively correlated with increased soil ammonium and alkali-hydrolyzable nitrogen. B9 likely contributed to ammonium accumulation via the dissimilatory nitrate reduction to ammonium (DNRA) pathway. Non-targeted metabolomics further indicated enhanced nitrogen and carbon metabolic activity in VB9 soils. These findings support the synergistic effect of microbial inoculants and organic amendments in improving organic matter turnover and nutrient cycling in urban soils. Further research is needed to assess this strategy’s long-term efficacy and ecological impact under field conditions.